Evaluation of hygienic food handling practices and associated factors among food handlers in the Amhara region, Ethiopia: a systematic review and meta-analysis - Lamenew Fenta; Kebadu Tadesse (Italian Journal of Food Safety)
Foodborne illnesses as a result of poor food handling practices pose a significant threat to public health. The main objective of this systematic review and meta-analysis was to pool the level of hygienic food handling practices among food handlers working in public food establishments in the Amhara region, Ethiopia. An inclusive search of databases was undertaken using PubMed/MEDLINE, SCOPUS, Web of Science, and Google Scholar from the 1st of January 2014 to the 30th of December 2023. Data was collected and entered into Excel and finally exported to Stata V.17 for analysis. Eyeball testing using forest plots, Cochrane Q test statistics and I² had been used to identify and measure heterogeneity. The pooled prevalence of hygienic food handling practices was estimated using a random effects model. The pooled prevalence of hygienic food handling practices of food handlers in the Amhara region was 48% [95% confidence interval (CI): (43%, 53%)] with significant heterogeneity (I2=94.39%, p<0.05). Food handlers who have more than 2 years of food preparation experience [odds ratio (OR) = 3.51; 95% CI (2.64, 4.38)] and who got food preparation training [OR=2.14; 95% CI (1.06, 3.22)] were significantly associated with good food handling practice in the Amhara region. The pooled prevalence of hygienic food handling practices was low in the Amhara region, Ethiopia. This review indicated that a high level of experience and training in food preparation were the determinants of good food handling practices in the region. This finding can be used by policymakers, non-governmental organizations, and stakeholders for intervention and regulatory measures.